ROLE OF IMMUNOMODULATORY AND BIOLOGICAL THERAPY IN THE TREATMENT OF PATIENTS WITH BEHCET'S UVEITIS -CASES FROM CLINICAL PRACTICE - Sekerinov, Natasa Trpevska; Markovska, Vesna Celeva; Pandilov, Stefan; Gucev, Filip (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Morbus Behcet is a multisystemic, chronic disease, vasculitis, of unknown etiology. The highest incidence is in the countries of the so-called â€œsilk roadâ€. In Macedonia, the frequency of this disease is currently unknown, but it is often under-diagnosed and unrecognized. In addition to the others, one of the main manifestations is ocular, which is presented by involvement of any of the structures of the uveal tract, the retina and the optic nerve. The diagnosis is established on the basis of clinical parameters, complemented by genetic analyses-HLA-B51 typing and Pathergy positive test and ophthalmic imaging-techniques such as OCT, OCT-A, FFA. Treatment of the condition is multidisciplinary with local and systemic corticosteroid therapy, conventional immunosuppressive drugs, and biological therapy. The aim of this paper is to present our experience in diagnosis and therapeutic modalities in patients with this disease. Keywords : uveitis, retinitis, Behcet's disease, azathioprine, cyclosporine, adalimumab